2018
DOI: 10.21276/ijcmsr.2018.3.2.38
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections in Elective Abdominal Surgery and their Prevention in a Tertiary Care Centre of Rohilkhand Region

Abstract: Inclusion criteria • All the patients undergoing elective abdominal surgery A B S T R A C T Introduction: Infections that occur in a postsurgical wound are referred to as Surgical Site Infections (SSIs) which results in patient discomfort, prolonged hospital stay and increased cost. The present study was planned to determine the risk factors and incidence of abdominal surgical site infections and to formulate measures to prevent them. Material and Methods: A prospective, open label clinical study of 24 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Pre-morbid illnesses, namely, diabetes and hypoalbuminemia, have been shown to have great risk of emerging SSI in the earlier studies; this was further confirmed in our study [12,26,31]. The incidence of SSI was found to be higher in open surgeries as compared to laparoscopic surgeries in our study similar to findings of other studies [16,32].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Pre-morbid illnesses, namely, diabetes and hypoalbuminemia, have been shown to have great risk of emerging SSI in the earlier studies; this was further confirmed in our study [12,26,31]. The incidence of SSI was found to be higher in open surgeries as compared to laparoscopic surgeries in our study similar to findings of other studies [16,32].…”
Section: Discussionsupporting
confidence: 91%
“…Wound class has been a significant predictor for SSI. The odds ratio of SSI increased with each class of wound in our study and other studies [8,12,15,16]. Albumin is a assessable sign of protein-energy malnutrition and has been connected with poor tissue healing, conceded immune response, and impaired collagen synthesis at operating sites [22,23].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation